Dukung Pemerintah Dengan Transformasi Pencegahan Dan Penanganan TBC Melalui Inovasi Aplikasi Digital: Upaya Edukasi Dan Sistem Monitoring - Zakiyah; Nisa, Sofatun; Rini, Niza Ayu Mustika; Aula, Afikatul; Amanullah, Mohamad Dafa; Maulidana, Abdul Jamal; Anam, Dimas Saeful; Ramadhan, Ilwan Qodri; Mazaya, Najwa Nida; Muthmainnah, Raisah; Lutfiah, Zulfa (Profetik: Jurnal Pengabdian Masyarakat, 2025)
Tuberculosis is a disease caused by the bacteria Mycobacterium Tuberculosis. Transmission occurs when sufferers talk, cough, sneeze or spit carelessly, which allows bacteria to spread into the air, then enter the body through the respiratory tract and spread to various other organs. Currently, Indonesia is in second place in the world after India, with an estimated number of TB cases of 1,060,000 and 134,000 deaths each year. Tegal Regency is one of the areas with a high caseload. The number of drug sensitive TB (SO) cases found in 2023 will reach 5,088 cases. The Head of the Department of Health said that collaboration on TB control must be carried out in an integrated manner by Forkopimda, OPD, academics, NGOs, mass organizations and the media in Tegal Regency, in order to accelerate the elimination of TB. So, as a form of participation in supporting government programs in accelerating the elimination of TB, IBN Tegal KKN students and DPL made breakthrough innovations in an effort to educate the public, prevent and treat TB by launching the digital application "Healthy Together Against TB". Community service through KKN activities is carried out using the ABCD method. The findings state that this innovation provides benefits: 1) Education on TB prevention and treatment as well as reporting to health workers that is easily accessible even in remote areas; 2) Medication reminder feature for TB patients; 3) Ease for health workers in recording, storing and updating patient data.